Coumarins as privileged scaffold for anti-inflammatory drug development. Issue 49 (30th May 2015) - Grover, Jagdeep; Jachak, Sanjay M.
<x xml:space="preserve">Abstract</x> Several literature reports had highlighted the significance of coumarin nucleus as a source of potential candidates for anti-inflammatory drug development.